Evaluation of psychosocial and biological parameters in women seeking for a caesarean section and women who are aiming for vaginal delivery: a cross-sectional study - Tuschy, Benjamin; Berlit, Sebastian; Stützer, Paul Philipp; Lis, Stefanie; Schmahl, Christian; Baumgärtner, Ulf; Sütterlin, Marc (Archives of gynecology and obstetrics, 2018)
PurposeTo investigate psychosocial and biological parameters that may influence decision-making concerning the mode of delivery in women with caesarean section on maternal request (CSMR).MethodsTwo hundred and two women were enrolled prospectively. The study sample (n = 93) consisted of women who aimed for CSMR, the control sample were women who seeked for vaginal delivery (n = 109). Parturients of both samples were enrolled during the pre-birth counselling at the delivery room at the University Medical Centre Mannheim, University Heidelberg, Germany. Women completed standardised questionnaires regarding psychosocial burden (SCL-R 90), fear of childbirth (W-DEQ) and anxiety (STAI), personality structure (HEXACO-Pi-R), and ambiguity tolerance (PFI, PNS, and NFC), social support (F-SozU) as well as one questionnaire assessing demographic parameters and further factors potentially influencing their choice of the mode of delivery. Hair cortisol concentration as a marker for chronic psychological stress and pressure pain threshold with a pressure algometer was assessed.ResultsWomen in the CSMR sample had less social support (F-SozU: 2.99 ± 0.52 vs. 3.12 ± 0.32; p = 0.043) and were less educated (high school or university degree: 37 vs. 71%, p = 0.001) compared to parturients of the control sample. Women who underwent CSMR were less open-minded (HEXACO-Pi-R: 3.08 ± 0.57 vs. 3.26 ± 0.50; p = 0.016) and less extroverted (HEXACO-Pi-R: 3.34 ± 0.36 vs. 3.46 ± 0.41; p = 0.041). The control collective showed higher scores in negative appraisal of the birth (‘W-DEQ-negative appraisal’: 2.5 ± 0.8 vs. 2.2 ± 0.9; p = 0.006), whereas “lack of positive anticipation” was higher in the study collective (‘W-DEQ-lack of positive anticipation’: 3.2 ± 1.2 vs. 2.8 ± 0.8; p = 0.015). The study collective had higher pressure pain threshold values (5.07 ± 2.06 vs. 4.35 ± 1.38; p = 0.007), while no significant differences were observed in hair cortisol concentration comparing both groups (5.0 ± 11.4 vs. 4.9 ± 8.3; p = 0.426). The majority of the control collective (80%) had chosen the vaginal route as their mode of delivery before pregnancy, whereas only 21% of the women in the study collective decided to undergo CSMR before conception. The advice of social sources including both medical and non-medical aspects was rated less important in the study sample, with significant differences indicating a lower relevance of counsel from friends (p = 0.002) and midwives (p < 0.001).ConclusionWomen who inquired a CSMR had lower social support, were less educated, more anxious, and had a lower sensitivity for physical pain compared to women seeking for spontaneous delivery. This should be considered when counselling women requiring CSMR and could be leverage points to intervene to reduce the continuously increasing CSMR rate.
Gesehen am 17.06.2019